2016
DOI: 10.1055/s-0036-1581055
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Hemoglobin A1c Prediction of Gestational Diabetes

Abstract: Objective The objective of this study is to examine whether a first trimester hemoglobin A1c (A1C) of 5.7 to 6.4% predicts an abnormal second trimester oral glucose tolerance test (OGTT). Methods We conducted a retrospective cohort study of all women screened with A1C through 13 (6/7) weeks' gestation between January 1, 2011, and December 31, 2012. Prediabetic women (A1C of 5.7-6.4%) were compared with women with a normal first trimester A1C (< 5.7%). The primary outcome was an abnormal 2-hour, 75-g OGTT as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 15 publications
6
16
1
Order By: Relevance
“…This optimal cutpoint maximizes the effectiveness of the test, but may not be ideal for the sole purpose of GDM diagnosis given that we have existing diagnostics based on the OGTT and the purpose of measuring HbA 1c would only be an earlier diagnosis. Nonetheless, at a cutpoint of 5.7% (39 mmol/mol), the current cutpoint for prediabetes outside of pregnancy, the sensitivity was 21%, but the specificity was very high at 95%, which is very similar to estimates reported in a prior study of 13% and 94%, respectively 6 . There are two important things to note from our findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This optimal cutpoint maximizes the effectiveness of the test, but may not be ideal for the sole purpose of GDM diagnosis given that we have existing diagnostics based on the OGTT and the purpose of measuring HbA 1c would only be an earlier diagnosis. Nonetheless, at a cutpoint of 5.7% (39 mmol/mol), the current cutpoint for prediabetes outside of pregnancy, the sensitivity was 21%, but the specificity was very high at 95%, which is very similar to estimates reported in a prior study of 13% and 94%, respectively 6 . There are two important things to note from our findings.…”
Section: Discussionsupporting
confidence: 85%
“…A few prior studies have examined if HbA 1c measured in the first trimester is useful for early predication of GDM 3 6 ; however, these studies have been among high-risk populations only 4 , 5 , evaluated an HbA 1c threshold only of 5.7% (39 mmol/mol), corresponding to prediabetes outside of pregnancy 6 , or used GDM diagnosed in the first trimester only as the outcome 3 . Other studies have focused primarily on HbA 1c measured in the second trimester or at the time of GDM diagnosis 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis Osmundson et al showed that risk for GDM was increased by 50% (adjusted RR, 1.48; 95% CI 1.15 to 1.89) in women with first trimester HbA1c of 5.7%–6.4% compared with women with an HbA1c in normal range. 17 Other studies concluded similarly that HbA1c levels referred for pre-diabetes outside of pregnancy are associated with GDM manifestation and hereby supported the prognostic applicability of HbA1c in GDM risk prediction. 6 7 18 Of interest, in a very recent retrospective cohort study pregravid HbA1c measured at median 1.4 years before pregnancy was shown to be a robust predictor of GDM.…”
Section: Discussionsupporting
confidence: 67%
“…Our observations of a relatively high specificity but low sensitivity at an HbA1c cut-off of 5.7% for GDM development are very similar to the findings of the retrospective study by Osmundson et al , who equally used the IADPSG criteria for GDM diagnosis and applied the same threshold for their analysis. 17 As far as applicable, we could further extract similar test characteristics (ie, specificity and sensitivity) for a cut-point of 5.7% from studies, which differ regarding to diagnosis criteria (ie, the two-step screening by Carpenter and Coustan criteria with preceding challenge test) and the primary choice of a lower threshold. 7 20 21 Further, it has to be considered that HbA1c changes throughout pregnancy 7 which may explain why only moderate correlations are detectable between early HbA1c and glucose examinations in third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…GDM was diagnosed by the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria using a one-step 75-g, 2-h OGTT. The results indicated a first-trimester HbA1c level of 5.7–6.4% was associated with a low sensitivity (13%) and a 94% specificity in the prediction of GDM [21]. In a study by Renz and colleagues, GDM was diagnosed by the World Health Organization (WHO) 1999 and American Diabetes Association (ADA)/WHO 2013 criteria.…”
Section: Discussionmentioning
confidence: 99%